An Ayurvedic Approach Towards Management of Female Infertility due to Anovulation (International Journal of Ayurveda and Pharma Research, 2023)
Infertility is becoming major issue in today’s society due to declining rate of fertility and fecund ability. In Ayurveda there are four important factors of Garbha that are Ritu (fertile period, season), Kshetra (healthy reproductive organs), Ambu (proper nutrient fluid), Beeja (ovum or sperm). Abeejatava in females can be correlated with decrease in quality and quantity of ovum i.e., anovulation. The development of follicle to appropriate size to become ovum and its rupture will take part in process of conception. Vitiation of Tridosha is responsible for anovulation. In this case a 33 year old female with case of Apraja with Beejadushti was anxious to conceive since 13 years of marital life came to OPD of Prasuti Tantra and Stree Roga at Sree Dharamasthala Manjunatheshwara Hospital, Hassan.Methodology: In this case Uttara basti with Prasarini taila for 3 days followed by oral administration of Chitrakadi vati was given. This protocol was followed for 3 consecutive menstrual cycles. Outcomes: The patient was having anovulation before the treatment. After the treatment follicle size increased upto 17mm. Conclusion: Ayurveda is effective in management of infertility due to anovulation.